2009
DOI: 10.1145/1462153.1462154
|View full text |Cite
|
Sign up to set email alerts
|

Recursive Markov chains, stochastic grammars, and monotone systems of nonlinear equations

Abstract: We define Recursive Markov Chains (RMCs), a class of finitely presented denumerable Markov chains, and we study algorithms for their analysis. Informally, an RMC consists of a collection of finite-state Markov chains with the ability to invoke each other in a potentially recursive manner. RMCs offer a natural abstract model for probabilistic programs with procedures. They generalize, in a precise sense, a number of well studied stochastic models, including Stochastic Context-Free Grammars (SCFG) and Multi-Type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
477
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 168 publications
(485 citation statements)
references
References 49 publications
8
477
0
Order By: Relevance
“…The formalism of recursive Markov chains [25] is used for describing recursive probabilistic processes. Alternatives are described using a Markov chain, where each node in the chain can be a call to another (or the same) chain.…”
Section: Recursive Markov Chainsmentioning
confidence: 99%
See 1 more Smart Citation
“…The formalism of recursive Markov chains [25] is used for describing recursive probabilistic processes. Alternatives are described using a Markov chain, where each node in the chain can be a call to another (or the same) chain.…”
Section: Recursive Markov Chainsmentioning
confidence: 99%
“…In particular, they showed that this task is tractable for the class of weakly linear SCFGs (that generalizes popular normal forms like linear SCFGs, and Chomsky or Greibach normal forms). It follows from known results [25] that, in the general case, query probabilities do not have a polynomial-size bit representation, and can even be irrational.…”
Section: Scfgsmentioning
confidence: 99%
“…A Recursive Markov Chain can be seen as a collection of finite-state Markov Chains with the ability to invoke each other, possibly in a recursive way. They have been introduced in [26] and come with a strong mathematical support. RMCs can be analyzed (by means of equation systems) in a very efficient way in order to evaluate reachability properties.…”
Section: Reliabilitymentioning
confidence: 99%
“…[7,8,10,13]). In all these applications the equations are interpreted over ω-continuous semirings, an algebraic structure that guarantees the existence of a least solution µf .…”
Section: Introductionmentioning
confidence: 99%